PERUBAHAN SIFAT FISIK DAN STABILITAS DIMENSI KAYU AKIBAT PENGAWETAN MENGGUNAKAN IMPREGNASI KARBONDIOKSIDA - Muhammad Asdar (Forestry Faculty of Universitas Hasanuddin, 2007)
The anatomical characteristics were studied to collect information for wood identification of Gyrinops versteegii from Gorontalo. Anatomical characterisics were determined from microtome sectioned samples and macerated samples. Observation of anatomical structure in accordance to IAWA List included vessel (diameter, height, grouping, frequention, porosity, arrangement, perforation plates, deposits, and pits), rays (type, height, width and frequention), parenchyme, and fiber (diameter, diameter of lumina and wall thickness). The research results obtained are G. versteegii has included phloem, diffuse porous, radial multiple 2-4(7), 90 µm in tangential diameter, 14 per sq.mm, simple perforation plates, intervessel pit alternate and no deposites in vessel. Rays uniseriate, heterocellular and 8,4 rays per mm. Axial parenchyma diffuse or associated with included phloem and there are fusiform parenchyma cells. Intercellular canals absent. This wood has short size and very thin walled fiber. Keywords: Agar wood, wood anatomy, included phloem, G. versteegii